The Carter Administration and the Fall of Iran's Pahlavi Dynasty US-Iran Relations on the Brink of the 1979 Revolution - Guerrero, Javier Gil.; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
During the first two years of Carter's presidency, Iran entered a spiral of violence and unrest that ended with the exile of the Shah and the establishment of an Islamic Republic. The Iranian revolution was first neglected by American diplomats and intelligence officials. When Carter finally became aware of the extent of the disturbances in Iran, he refused to explicitly back the iron fist policy sought by the Shah. The Iranian monarch was unwilling to decisively tackle the protests without Carter's blessing and thus he proceeded with a failed policy that mixed concessions with repression, which only served to postpone the inevitable. This book looks at recent declassified documents from several archival resources that provide an unprecedented picture of the Carter administration's uneasiness regarding the Shah's Iran. Gil Guerrero analyzes the disputes between Washington and Tehran concerning human rights and arms exports, the divisions inside the White House, and the Shah's uncertainty regarding Carter's support. The sources gathered all point to a late process of political liberalization encouraged by American officials that only served to weaken the Shah's authority while emboldening the opposition, in the words of Ayatollah Khomeini, to 'seize the moment." They offer an unprecedented picture of the forces that enabled Khomeini's triumph, altered America's perception of Islam, and fundamentally changed the United States' relationship with Iran.
Keywords: Middle East-Politics and governm; Middle East-History.; Islam; International relations; United States-History.; Political theory